Health Helper: technology for measuring blood flow and blood pressure - Samus, Pavlo (My University, 2023)
This research proposes integrating Health Helper, a startup aiming to reduce premature deaths caused by cardiovascular diseases, into the European Scientific Space through blockchain technology. A five-phase roadmap is outlined for the project, with enormous potential for reducing premature deaths and contributing to Ukraine's integration.
Keywords: Health Helper; cardiovascular diseases; diagnostic device; blockchain technology; five-phase roadmap; European Scientific Space; startup